Applications of Biosorption in Wastewater Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book examines the state of the art of biosorption as an economical and environmentally friendly technique for pollutant removal in wastewater. Several articles are included that develop the applications of biosorption showing the high efficiency and versatility of this process, as well as showing recent advances in this field. Different modalities of biosorption are demonstrated from free biomass to immobilized biomass, as well as the combination of biomass with modern materials to form composites, emphasizing the significant versatility of this technique. In addition, different examples with biomasses of very different natures are also included and discussed, as are the factors that influence biosorption processes. Other contributions offer some examples of apparently useless materials that are reused and applied in the elimination of pollutants. Therefore, this book is an excellent complement for those researchers who work on biosorption as well as a starting point for those who want to begin research on this topic.